Implementation of the Articulation Learning Model to Enhance the Understanding of Grade X-3 Students in Indonesian History Learning at SMA Negeri 2 Medan Academic Year 2023-2024. - Safitri, Intan; Nugraha, Muhammad Adika; Aisyah, Sitti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The Implementation of the Articulation Learning Model to Enhance Grade X-3 Students' Understanding in Indonesian History Learning at SMA Negeri 2 Medan Academic Year 2023-2024. Many students perceive history learning as a monotonous subject, merely involving memorizing sequences of events and figures without relevance to everyday life. History education is considered crucial for nurturing the character of the nation's generation. However, at SMA Negeri 2 Medan, there are still students who are less active in learning, especially when using specific teaching models. The purpose of this study is to enhance the understanding of grade X-3 students in Indonesian History learning by implementing the articulation learning model. The research was conducted through the Classroom Action Research (CAR) method with grade X-3 students at SMA Negeri 2 Medan as the research subjects. The results indicate an increase in students' activity and understanding from cycle to cycle. In cycle I, student activity reached 41%, in cycle II it reached 68%, and in cycle III, student activity reached 78%. Similarly, students' understanding or learning outcomes also increased in each cycle. In cycle I, 61% or 22 students obtained a score 70, in cycle II, there was an increase to 75% or 29 students obtaining a score 70, and in cycle III, there was a further increase to 94% or 34 students obtaining a score 70. In cycle III, student activity reached 78%, and 94% of students obtained a score 70, meeting the established proficiency criteria.